Nutrition in Kidney Disease - Byham-Gray, Laura D.; Burrowes, Jerrilynn D.; Chertow, Glenn M. (Nutrition and Health, 2008)
The field of kidney disease has evolved over the years to encompass a broad and sophisticated knowledge base. There has been a proliferation of scientific information and technical advances in the field. In Nutrition in Kidney Disease, the authors provide a comprehensive perspective of the emerging science in nutrition in kidney disease. This important book is written by a collaborative group of distinguished dietitians and physicians in the specialized field of kidney disease and clinical nutrition, who have devoted their careers to the care of patients with kidney disease. At the end of key chapters, case studies assess knowledge of the subject within the context of didactic curriculums. Part I addresses kidney function in health and disease. Parts II and III provide in-depth information on the prevention of common disorders associated with chronic kidney disease, current treatment options based on the latest scientific evidence, and management, while Part IV presents the nutrition concerns of special needs populations. Part V addresses additional nutritional concerns in kidney disease such as complementary and alternative medicine, cultural issues affecting dietary adherence, and outcomes research. Nutrition in Kidney Disease provides today's most valuable reference as well as operative tool for the practicing clinician in the fields of nutrition and nephrology, as well as other disciplines whose research, practice, and education include nutrition.